The Impact of Introducing a Minimum Wage on Business Cycle Volatility : A Structural Analysis for Hong Kong SAR. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
We study the impact of a minimum wage on business cycle volatility, depending upon its coverage and adjustment mechanism. As with other small open economies, Hong Kong SAR is vulnerable to external shocks, with its exchange rate regime precluding active monetary policy. Adjustment to past shocks has relied on flexible domestic prices. We find that a minimum wage affecting 20 percent of employees would amplify output volatility by 0.2 percent to 9.2 percent, and employment volatility by ?1.2 percent to 7.8 percent. A fixed wage or indexation to consumption price inflation increases volatility most. Indexation to wage inflation or unit labor cost growth is preferable, largely preserving labor market flexibility.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet